The Implementation of Tactical Approach on Students' Enjoyment in Playing Football in Junior High School - Sucipto Sucipto (JURNAL PENDIDIKAN JASMANI DAN OLAHRAGA, 2019)
The purpose of this study was to examine the implementation of a tactical approach in improving students’ enjoyment in playing football in junior high school. The method used in this study was an experimental study with a posttest control group design. The study involved two groups, one experimental group with a tactical approach intervention and one control group with a technical approach intervention to develop their enjoyment. The instrument used was an enjoyment scale. The study was conducted in a junior high school in Bandung. The obtained data were analyzed by the independent sample t test technique to see differences between the influence of tactical and technical groups on developing students’ enjoyment. The results of the analysis proved that there was a significant difference between the tactical and technical groups on enjoyment in playing football that is seen from the mean difference (10.82). It shows that tactical approach was proved to have a higher and significant effect than the technical groups on student enjoyment in soccer learning. In other words, the implementation of tactical approach has an influence on the students' enjoyment in soccer learning.   AbstrakPenelitian ini bertujuan untuk menguji penerapan pendekatan taktis dalam pengembangan kesenangan bermain sepak bola siswa SMP. Metode yang digunakan dalam penelitian ini adalah eksperimen dengan rancangan posttest control group design. Dengan melibatkan dua kelompok, yaitu satu kelompok eksperimen dengan intervensi pendekatan taktis dan satu kelompok kontrol dengan intervensi pendekatan teknis terhadap pengembangan kesenangan. Instrument yang digunakan adalah instrument skala kesenangan. Penelitian dilakukan pada siswa-siswi SMP dilingkungan kota Bandung. Data yang diperoleh analisis dengan menggunakan teknik independent sampel t test yang bertujuan untuk melihat perbedaan pengaruh antar kelompok taktis dan teknis terhadap pengembangan kesenangan siswa. Hasil analisis terbukti bahwa terdapat perbedaan yang signifikan antara kelompok taktis dan teknis terhadap kesenangan bermaian sepakbola, dilihat dari mean difference diperoleh selisih sebesar 10,82, artinya bahwa kelompok taktis terbukti berpengaruh lebih tinggi dan signifikan dari pada kelompok teknis terhadap kesenangan siswa dalam pembelajaran sepak bola. Dengan kata lain penerapan pendekatan taktis memberikan pengaruh terhadap kesenangan siswa dalam pembalajaran sepak bola.